ANALISIS DAMPAK BERMAIN GAME ONLINE TERHADAP AKHLAK REMAJA (STUDI TRADISI DESA MAKARTI MULYA, MESUJI, OKI, SUMSEL). - Afifuddin Ahmad Robbani; Adi Wijaya (Jurnal Pendidikan Islam, 2026)
This article examines morality which means temperament, customs or behavioral systems that are created. While the purpose of this study is to determine the analysis of the dangers of playing Online Games on the Morals of Teenagers in Makarti Mulya Village, Mesuji District, Ogan Komering Ilir Regency. This study uses a qualitative descriptive approach method, researchers use two sources, namely the first from primary data, researchers get data from informants, namely parents of teenagers addicted to online games and religious figures. The second is secondary data, namely obtaining documents, in the form of archives such as the profile of Makarti Mulya Village, Mesuji District, Ogan Komering Ilir Regency (Oki). The Results of This Study Researchers Found That the dangers of online games for adolescent communication morals are caused by the main factor causing the teenagers themselves, the lack of assertiveness from parents in the problem of using smartphones. The lack of an approach from parents triggers the teenager at home to play smartphones more freely and without supervision. When they are out of parental supervision at home, it is very potential that teenagers will not know the time in playing online games on smartphones. And so on.